Scalp Micro-Pigmentation via Transcutaneous Implantation of Flexible Tissue Interlocking Biodegradable Microneedles - Fakhraei Lahiji, Shayan (Pharmaceutics, 2019)
Alopecia, characterized by hair follicle blockage and hair loss, disrupts the normal cycle of hair growth. Although not a life-threatening condition, a growing body of evidence suggests that the psychological state of individuals experiencing alopecia can be highly influenced. Despite considerable research on hair loss treatment, interest in micro-pigmentation has increased in recent decades. Micro-pigmentation is an effective method to camouflage the visual contrast between the scalp and hair strands. However, the localization, intensity and dimension of microdots depend highly upon the physician performing the implantation. Incorrectly localized microdots within the skin may lead to patchy or faded micro-pigmentation. To overcome the limitations of conventional micro-pigmentation, we aimed to develop micro-pigment-encapsulated biodegradable microneedles (PBMs), capable of accurately implanting pigments below the epithelial-dermal junction of the scalp in a minimally invasive manner. A tissue interlocking microneedle technique was utilized to fabricate double-layered PBMs over a biodegradable flexible sheet, which could be washed off post-implantation. We confirmed that the intensity, dimension and insertion depth of 1000 μm-long PBMs was maintained on pig cadaver skin over time. This study suggested that the developed PBMs would serve as an attractive platform for scalp micro-pigmentation in the future.